Analysis Of Technology Needs Of Msmes In The Fisheries Industry In Pekalongan City: A Digital Transformation-Based Approach And Increasing Competitiveness - Angkasa, Wisman Indra; Tabrani, Tabrani (Al-Makki Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in local economic development, including the fisheries sector in Pekalongan City. However, low adoption of modern technology hampers productivity and competitiveness of fisheries MSMEs in this region. This study aims to identify the most pressing technological needs and assess the readiness of fisheries MSMEs to adopt digital transformation. The research method used a mixed methods approach through a survey of 30 MSMEs, in-depth interviews with stakeholders, and field observations. Data were analyzed using descriptive statistics, GAP analysis, Technology Readiness Level (TRL), and SWOT analysis. The research results show that the majority of MSMEs (86%) have not utilized digital technology in their production, packaging, or marketing processes. Three key technological needs identified include: (1) renewable energy-based drying machines to increase production efficiency; (2) vacuum packaging equipment to maintain product quality and extend shelf life; and (3) digital marketing and e-commerce platforms to expand market access. The main inhibiting factors are low digital literacy, limited capital for technology investment, and minimal training and technical assistance. These findings align with previous studies that emphasized the importance of digital transformation as a key to improving the competitiveness of fisheries MSMEs. This research recommends several strategies, including routine technology-based training, facilitating financing for technological equipment procurement, and strengthening partnerships between MSMEs, the government, and local technology startups. In conclusion, accelerating digital transformation through appropriate technology can significantly increase the productivity and competitiveness of fisheries MSMEs in Pekalongan City, as well as support the achievement of sustainable development goals (SDGs) in the areas of industrial innovation and decent work.